The Third-Year Preview Program: A Near-Peer Shadowing for Second-Year Students with Third-Year Medical Students - Alexander Vogel; Samantha Gelfand; Robert Fallar; Peter Gliatto; Reena Karani (Association of American Medical Colleges, 2014)
Abstract Introduction New clinical students feel a profound amount of stress and anxiety as they transition to the clinical workplace setting. Peer-assisted learning has been shown to be useful in helping to effectively educate medical students. However, no peer-assisted learning model has been developed to prepare second-year students for this transition and to reduce the anxiety associated with it. The Third-Year Preview Program was designed to prepare students for third year by providing them with tangible skills and to decrease their anxiety through an in-person immersion with a third-year student on the wards. Methods From recruitment through assessment of efficacy, this curriculum directs the successful implementation of a near-peer shadowing program linking second-year students with third-year students. Materials include sample recruitment tools, a guide given to both mentor and mentee to help shape the day, and a survey to assess the efficacy of the program. The survey has three parts. Self-reported skill and knowledge improvement are assessed by questions presented as a 5-point Likert-type scale (from disagree to agree). Students' perceived anxiety towards the transition to third-year is assessed by an adapted version of a published and validated perceived anxiety scale. Finally, open-ended questions give participants the opportunity to reflect on the program as a whole. Results Of the 25 students who participated in the program, 21 (84%) completed the survey. While the sample size was small, the results overwhelmingly suggested that in just half a day, the Third-Year Preview Program can make a meaningful difference for second-year students by helping them prepare for third year and can alleviate significant anxiety by allowing them to experience what third year is truly like. Discussion It has been well documented in the literature that students feel significant anxiety in regard to transitioning to the clinical work space from the classroom setting. Our data suggest that the Third-Year Preview Program can meaningfully decrease anxiety for students and let them start third year with more confidence.